2022
DOI: 10.1002/iju5.12517
|View full text |Cite
|
Sign up to set email alerts
|

A case of robot‐assisted adrenalectomy performed for an adrenal tumor (anastomosing hemangioma) exceeding 7 cm

Abstract: Introduction: Anastomosing hemangioma in the adrenal area is extremely rare. We report a large anastomosing hemangioma in the adrenal area that underwent robotassisted adrenalectomy. Case presentation: A 49-year-old man with left back pain underwent magnetic resonance imaging (MRI) that revealed a tumor in the left adrenal area; it was diagnosed as nonfunctional endocrinologically. However, the major axis of the tumor increased from 64 to 72 mm during the 4-month period. Robot-assisted left adrenalectomy was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Interestingly, none of the patients have presented with a haemorrhagic incident. The largest lesion reported so far was 7.2×6.4×5.6 cm in size by Nishikimi et al and the patient underwent robot-assisted left adrenalectomy 11. All diagnoses were confirmed at adrenalectomy except one where CT-guided biopsy was performed 22…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Interestingly, none of the patients have presented with a haemorrhagic incident. The largest lesion reported so far was 7.2×6.4×5.6 cm in size by Nishikimi et al and the patient underwent robot-assisted left adrenalectomy 11. All diagnoses were confirmed at adrenalectomy except one where CT-guided biopsy was performed 22…”
Section: Discussionmentioning
confidence: 92%
“…Since then, around 64 cases of AH have been reported, adrenal as a site for AH was first described by Ross et al 10. Since then, only 15 cases have been reported; the largest being a case series of 7 cases in a retrospective 25-year analysis of adrenal pathologies at the Cleveland Clinic 11–17…”
Section: Discussionmentioning
confidence: 99%
“…7 To date, 10 anastomosing haemangiomas of the adrenal gland have been reported, 5,7-12 but two were actually periadrenal soft tissue in location. 13,14 In Table 2, we present clinicopathological and radiological findings from six of the eight reported cases of adrenal anastomosing haemangioma for which the data were available. The mean age of patients in our study (61 years, range = 37-75) was higher than that reported in the literature (49 years, range = 32-68), while the gender distribution was similar.…”
Section: Discussionmentioning
confidence: 99%
“…The true incidence of anastomosing haemangioma in the adrenal gland is not known, due to its rarity, but estimates suggest that 3–4% of all anastomosing haemangiomas arise in the adrenal gland 7 . To date, 10 anastomosing haemangiomas of the adrenal gland have been reported, 5,7–12 but two were actually peri‐adrenal soft tissue in location 13,14 . In Table 2, we present clinicopathological and radiological findings from six of the eight reported cases of adrenal anastomosing haemangioma for which the data were available.…”
Section: Discussionmentioning
confidence: 99%